A Qualitative Rapid Detection of Sus scrofa DNA using Loop- Mediated AMPlification (LAMP) Isothermal Assay for Halal Food and Drug Detection at the Point-of-Care (Bangladesh Journal of Medical Science, 2026)
Background Halal authentication is critical in Muslim-majority markets, where pork contamination raises significant religious and regulatory concerns. Biomolecular techniques have been widely employed for halal detection in foods and drugs; however, challenges remain in sample handling, method validation, data interpretation, and technical limitations. Objective This study developed a modified loop-mediated isothermal amplification (LAMP) assay for detecting Sus scrofa DNA across various meat matrices at various dilutions. Methodology Specific modified LAMP primers were designed using the D-loop mitochondrial region. DNA was extracted from pork meat and nonpork meat using modified protocols. The LAMP assay’s sensitivity was tested down from 10-fold to 100,000-fold dilution. PCR reactions were done on the same sample with various dilutions as confirmation. Results Our modified LAMP with specific primers detected Sus scrofa DNA qualitatively and quantitatively with high specificity and no crossreactivity as sensitively as PCR reactions. It detected qualitatively and quantitatively Sus scrofa DNA up to 100,000x dilution (0.00286 ng/ μL), exceeding PCR’s detection limit. Visual detection with HNB dye showed clear color changes in the LAMP reaction, easing the rapid qualitative detection of Sus scrofa DNA, making LAMP an effortless and rapid screening for non-halal food or drugs. Subsequently, our results have shown that the sensitivity and the specificity of LAMP reactions compared to the PCR reactions are 100% and 100%, respectively. Thus, compared to PCR, LAMP was faster, highly sensitive, highly accurate, and field-deployable in the point-of-care setting. Conclusion LAMP is a sensitive, cost-effective, and equipment-independent technique suitable for qualitative adulteration detection in field and low-resource settings at the point-of-care.BJMS, Vol. 25 No. 02 April’26 Page: 518-525